2017
DOI: 10.12973/ejmste/78085
|View full text |Cite
|
Sign up to set email alerts
|

Test of Understanding Graphs in Calculus: Test of Students’ Interpretation of Calculus Graphs

Abstract: Studies show that students, within the context of mathematics and science, have difficulties understanding the concepts of the derivative as the slope and the concept of the antiderivative as the area under the curve. In this article, we present the Test of Understanding Graphs in Calculus (TUG-C), an assessment tool that will help to evaluate students' understanding of these two concepts by a graphical representation. Data from 144 students of introductory courses of physics and mathematics at a university wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
7
0
2
Order By: Relevance
“…A decade later, Beichner [47] designed the test of understanding graphs in kinematics (TUG-K), a multiplechoice test based on six dimensions corresponding to different categories of typical students' mistakes that he identified: graph as picture errors, confusion between slope and height, variable confusion, non-origin slope errors, area ignorance, and confusion among area, slope, and height. Recently, Zavala et al [48] have proposed a modified version of the TUG-K improving the parallelism between the different dimensions of the test, and Dominguez et al [49] have developed the test of understanding graphs in calculus (TUG-C), the counterpart of the TUG-K in a purely mathematical context.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A decade later, Beichner [47] designed the test of understanding graphs in kinematics (TUG-K), a multiplechoice test based on six dimensions corresponding to different categories of typical students' mistakes that he identified: graph as picture errors, confusion between slope and height, variable confusion, non-origin slope errors, area ignorance, and confusion among area, slope, and height. Recently, Zavala et al [48] have proposed a modified version of the TUG-K improving the parallelism between the different dimensions of the test, and Dominguez et al [49] have developed the test of understanding graphs in calculus (TUG-C), the counterpart of the TUG-K in a purely mathematical context.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Some researchers (Amit, & Vinner, 1990;Asiala, Cotrill, Dubinsky, & Schwingendorf, 1997;Dominguez, Barniol, & Zavala, 2017) discuss specific difficulties that students have with the graphical representation of the derivative. These authors explain some difficulties students have with basic calculus concepts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Third, we designed a written test comprised of 4 questions to compare the performance of the experimental group with the performance of another equivalent student group (control group). The test was designed by consulting relevant resources in mathematics education, in particular the teaching and learning of derivative (e.g., Asiala et al, 1997;Cooley et al, 2007;Dominguez et al, 2017).…”
Section: "(1) It Differs From Most Mathematics Education Research In mentioning
confidence: 99%
“…Previous studies reported although students' procedural knowledge about differentiation is usually adequate, most of them have little intuitive or conceptual knowledge of the derivative (Asiala, Cottrill, Dubinsky, & Schwingendorf, 1997;Clark et al, 1997;Dominguez, Barniol, & Zavala, 2017;Ferrini-Mundy & Graham, 1994;Orton, 1983;Tall, 1993;Thompson 1994;Uygur & Özdaş, 2005). It seems that several students perform poorly because they are unable to adequately handle information given in symbolic form which represents abstract entities, for example functions, or/and they lack adequate schema or frameworks, which helps to organize and link different objects (Maharaj, 2005).…”
Section: Introductionmentioning
confidence: 99%